The self-perception of employees' corporate communication and the relationship with their personal health (Research, Society and Development, 2021)
Corporate communication has been increasingly studied in recent decades and for it to occur effectively, it is essential that it flows through all departments without noise, since the communication practiced affects the results of the entire company. The objective of this research was to identify the self-perception of corporate communication by employees of Company X and its relationship with their personal health. Therefore, a case study was carried out in a food products company located in the city of Ji-Paraná, Rondônia. The collection date took place through semi-structured interviews with 13 employees of Company X. For data analysis, the Content Analysis method by Laurence Bardin was adopted. The results indicate that corporate communication is seen as positive by employees, despite disruptions in the communication flow. The position of opposing or contesting a colleague is dualistic, there are those who do it calmly and those who feel uncomfortable in carrying out this attitude. As for the self-perception of health, it is remarkable that some people interviewed note that there is a relationship between the corporate environment and their health, while others said that there is not, despite reporting indicators that point to a noticeable level of work stress.